2015
DOI: 10.1039/c5cc00823a
|View full text |Cite
|
Sign up to set email alerts
|

Anion transport across varying lipid membranes – the effect of lipophilicity

Abstract: The anion transport properties of a range of alkyl-substituted phenylthioureas were tested in vesicles of different lipid composition. Although changes in the bilayer affected the rate of transport for all compounds in the series, the 'ideal' log P for peak activity did not change depending on the composition of the bilayers tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 23 publications
0
45
1
Order By: Relevance
“…These results demonstrate that altering the structure of the hydrophobic portion of lipids can dramatically affect membrane leakage. Additionally, previous computational and experimental studies suggest that lipid headgroups affect membrane permeation of water, but have little effect on permeability of small organic molecules across membranes . However, to our knowledge no systematic study on the effects of headgroups on small‐ion permeability has been reported.…”
Section: Figurementioning
confidence: 90%
“…These results demonstrate that altering the structure of the hydrophobic portion of lipids can dramatically affect membrane leakage. Additionally, previous computational and experimental studies suggest that lipid headgroups affect membrane permeation of water, but have little effect on permeability of small organic molecules across membranes . However, to our knowledge no systematic study on the effects of headgroups on small‐ion permeability has been reported.…”
Section: Figurementioning
confidence: 90%
“…This may indicate that there are other mechanisms aside from ion transport that are responsible for the antibacterial activity in S. aureus or that there are differences between the properties of the model membranes used in this study and the bacterial membrane. 17 Further study of these and other anion transporters are on-going in an effort to elucidate more fully the underlying mechanisms of action and to develop more active receptor-based antibiotic agents.…”
mentioning
confidence: 99%
“…In order to properly understand this situation, the self‐assembling potential of the carrier and the complete transport mechanism needs to be considered. When a carrier has to pass through a lipid membrane it should be lipophilic enough as to be able to diffuse into the membrane, but not too much lipophilic as to aggregate in water or to be retained inside the lipid bilayer, hence resulting in the slower transport of the associated anions 24. The existence of an optimal range for lipophilicity for effective transport has been observed in other instances 25…”
Section: Resultsmentioning
confidence: 95%